Open source systems : 15th IFIP WG 2.13 international conference, OSS 2019, Montreal, QC, Canada, May 26-27, 2019, Proceedings /: 15th IFIP WG 2.13 international conference, OSS 2019, Montreal, QC, Canada, May 26-27, 2019, Proceedings. ([2019]) - Unknown
No abstract available